Basal cell carcinoma—a clinical indicator of immunosuppression - Scurtu, Lucian G.; Petrica, Marian; Scurtu, Francesca; Simionescu, Anca Angela; Popescu, Marco I.; Simionescu, Olga (Frontiers in Medicine, 2024)
Background: Basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) are skin-derived carcinomas. The literature strongly connects SCC with acquired immunosuppression. Current data regarding BCC's association with immunosuppressive comorbidities are vague. The primary objective of this study was to establish the correlations between BCC and immunosuppressive comorbidities of patients. Materials and methods: We conducted a retrospective cohort study on 275 patients with a histopathological proven diagnosis of BCC from October 2019 to October 2023. Demographic data, BCC characteristics, and patients' comorbidities were analyzed. Comorbidities were classified as nonimmunosuppressant and immunosuppressant (primary and secondary immunodeficiencies). Results: We recorded 292 BCCs from 275 patients (142 females, 133 males), with equally distributed skin phototypes. 66.44% of the BCCs were detected in patients with various comorbidities (p<0.001), of which 81.44% had immunosuppressive comorbidities (p<0.001). All the immunosuppressive comorbidities were secondary and included diabetes mellitus (47.55%), history of solid or hematogenous cancer in the last 5 years (26.57%), chronic kidney disease (8.39%), chronic infections (9.09%), and antirheumatic immunosuppressive therapies (8.39%) (p<0.001). BCC patients with immunosuppressive comorbidities did not develop larger BCCs (p=0.2577) or more aggressive subtypes (p=0.4269) and BCC did not arise earlier in their life (p<0.001). BCC on the nasal pyramid was frequent in cancer history patients (p=0.008). The ulcerated form of BCC is more confined to patients with chronic kidney disease (p=0.006). Multiple BCCs are more frequent in patients with secondary immunodeficiencies (p=0.027). Conclusion: BCC represents a clinical indicator of secondary immunodeficiency. Further research should establish if cancer screening campaigns may be beneficial in BCC patients.